Survival and mortality rates of Wilms tumour in Southern and Eastern European countries: Socioeconomic differentials compared with the United States of America. (September 2018) - Doganis, Dimitrios; Panagopoulou, Paraskevi; Tragiannidis, Athanasios; Vichos, Theodoros; Moschovi, Maria; Polychronopoulou, Sofia; Rigatou, Efthimia; Papakonstantinou, Eugenia; Stiakaki, Eftichia; Dana, Helen; Bouka, Panagiota; Antunes, Luis; et al.
Abstract: Background: Despite recent therapeutic advancements, Wilms tumour (WT) presents remarkable survival variations. We explored mortality and survival patterns for children (0–14 years) with WT in 12 Southern and Eastern European (SEE) countries in comparison with the United States of America (USA). Methods: A total of 3966 WT cases (0–14 years) were registered by a network of SEE childhood cancer registries (N:1723) during available registration periods circa 1990–2016 and surveillance, epidemiology, and end results program (SEER) (N:2243; 1990–2012); mortality data were provided by the respective national statistical services. Kaplan–Meier curves and Cox proportional hazards models were used to assess the role of age, sex, year of diagnosis, urbanisation and Human Development Index (HDI) on overall survival (OS). Results: Persisting regional variations shape an overall 78% 5-year OS in the participating SEE countries, lagging behind the USA figure (92%, p=0.001 ) and also reflected by higher SEE mortality rates. Worth mentioning is the gradually escalating OS in SEE (hazard ratio [HR]5-year increment :0.67, 95% confidence interval [CI]:0.60, 0.75) vs. a non-significant 10% improvement in the SEER data, which had a high starting value. OS differentials [two-fold less favourable among children aged 10–14 years, boys and those living in rural SEE areas (HR:1.37; CI:1.10–1.71) or countries with inferior HDI (2–3-fold)] were minimal in the USA. Conclusions: Children with WT residing in SEE countries do not equally enjoy the substantial survival gains, especially for those living in rural areas and in lower HDI countries. Noteworthy are steep and sizeable survival gains in SEE along with the newly presented Greek data pointing to achievable survival goals in SEE despite the financial crisis. Highlights: Wilms tumour (WT) survival varies among Southern and Eastern European (SEE) countries. Mortality rates for renal tumours are higher in SEE in comparison with the United States of America. Survival for WT patients in SEE countries has improved in recent years. Age, gender, rural residence and socioeconomic factors affect survival in SEE. Overall survival for WT in Greece was high and comparable to that of SEER.